EDUCATION POLICY ANALYSIS AFTER THE COVID-19 PANDEMIC IN ELEMENTARY SCHOOL - Yulfia Nora; Ira Rahmayuni Jusar; Adek Nilasari Harahap; Rusdinal Rusdinal; Nurhizrah Gistituati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
his research was conducted to identify and analyze educational policies after the pandemic in elementary schools. The education policy refers to law no. 20 of 2003 which aims to build the foundation of an intact nation so that good educational standards are realized. This law is in line with law no. 23 of 2014 which states that regional government has authority in educational services. The method in this study was carried out using descriptive qualitative. This method is used to describe the policies implemented after Covid 19. The analysis was carried out through the results of observations and interviews at three elementary schools in Padang. The results of this study indicate that post-covid-19 education policies in elementary schools are taken from regional head policies that are autonomous in nature related to educational supervision during the outbreak by monitoring elementary schools to demonstrate face-to-face school preparation. Obstacles in implementing educational policies stem from limited communication with students in terms of explaining material that demands to complete curriculum achievements.